Discovery of Cynipidae (Hymenoptera: Cynipoidea) from the Indochina Region, with Description of Three New Species. (1st March 2014) - Abe, Yoshihisa; Ide, Tatsuya; Konishi, Kazuhiko; Ueno, Takatoshi
Abstract: Plagiotrochus indochinensis Abe, Ide, Konishi, & Ueno sp. nov., Dryocosmus okajimai Abe, Ide, Konishi, & Ueno sp. nov., and Synophrus vietnamensis Abe, Ide, Konishi, & Ueno sp. nov. are described from Vietnam. This is the first record of Cynipidae (Hymenoptera: Cynipoidea) from the Indochina region; the former two species belong to tribe Cynipini and the latter to the inquiline tribe Synergini. Based on the observation of a female P. indochinensis inserting its ovipositor into a young sprout of Quercus ( Cyclobalanopsis ) helferiana A. de Candolle in the field, this wasp species is considered to induce galls on this evergreen oak species. This article confirms that members of Cynipini that induce galls on Cyclobalanopsis (the ring cup oaks) are widely distributed in Asia, as predicted previously. Although D. okajimai was collected by sweeping an evergreen Fagaceae tree, its host remains to be clarified. Because the adults of S. vietnamensis were collected by sweeping an evergreen Fagaceae tree in June and dissecting a bud gall on Castanopsis sp. in September, it is considered that this wasp species has more than one generation a year. The gall-inducing ability and host plant specificity of S. vietnamensis should be examined carefully in future. The high species richness of Quercus L. and related genera in the Indochina region increases the likelihood of the existence of little-known, but potentially diverse, cynipid fauna in this region.